Diabetes care in individuals with severe mental Illnesses in Israel. (13th November 2019) - Sagy, Y Wolff; Krieger, M; Horwitz, E; Paltiel, O; Ravel-Vilk, S; Ben-Yehuda, A; Manor, O; Calderon-Margalit, R
Abstract: Background: Cardiovascular disease and risk factors are more common in people with severe mental illness (SMI; schizophrenia, schizoaffective disorders, and bi-polar disorders). For instance, diabetes mellitus (DM) prevalence was reported to be 2-3 times higher, with higher incidence and severity of complications. In 2015, following a reform in mental health services in Israel, services were transferred to the responsibility of the health plans, allowing a comprehensive healthcare. We aimed to compare quality of care indicators and intermediate DM outcomes in individuals with SMI compared to the general population. Methods: The Israel national program for quality indicators in community healthcare obtains data from electronic medical records from the four health plans, covering the entire civilian population. In 2017, n = 74, 226 individuals aged ≥18 years had a registered diagnosis of SMI (prevalence 1.37%). DM prevalence, hemoglobin A1c (HbA1c) testing yearly, and DM control in individuals with SMI were compared with the general population. Results: DM prevalence in adults with SMI in 2017 was 14.3%, compared with 9.7% among all Israeli adults (RR of 1.5). rates of HbA1c testing and control (HbA1c<7-8%, depending on age and duration of disease) were similar among DM patients with SMI and the general population (testing: 90.1% and 90.9%; Control: 70.8% and 69.7%, SMI and general population, respectively); Similarly, uncontrolled DM (HbA1c>9%) was observed in 10.8% of individuals with SMI and in 10.0% of the general population. Conclusions: Along with the expected excess of DM prevalence in individuals with SMI, quality of care DM indicators rates were alike among those with SMI as in the general population, suggesting non-inferior quality of care. This is consistent with results reported by the British national diabetes audit for England and Wales. However, our results are limited by a possible under-registration or diagnosis of SMI in the Israeli population. Key messages: Higher diabetes mellitus prevalence is observed in individuals with severe mental illness. Hemoglobin A1c testing and diabetes mellitus control rates are alike in individuals with severe mental illness compared with the general population, suggesting non-inferior quality of care.